Identifying barriers of Implementing BIM in Construction - Oyarhossein, Mohammad Amin; Bayat Ghiasi , Seyed Hamid; Khiali, Vahid (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
New methods of construction projects to increase quality, reduce time and thus reduce costs have always been considered by construction engineers and stakeholders in the project. One of these new methods and technologies is building information modeling (BIM). The purpose of this study is to review and analyze the building information modeling (BIM) method and prioritize the factors affecting the challenge in establishing this system in the country. For this purpose, while determining the failure factors in the implementation of building information modeling system according to experts and through a questionnaire, the weight and importance of these factors were determined using the network analysis process (ANP) model and the factors were prioritized. The results obtained according to the opinions of experts and according to a binary comparison of the main criteria studied showed that the most factors that cause the failure of BIM in construction projects include technical, financial, human resources and time problems, respectively. Other results showed that four sub-criteria of information dispersion and lack of integrated system with a weight of 0.2277, complex program space with a weight of 0.1634, high design cost with BIM software with a weight of 0.1578 and the need for different office staff for a project weighing 0.1352 Sequence has been the most important and therefore the most influential in prioritizing the factors of BIM failure. By identifying the effective causes of the challenges of non-realization of BIM, preventive measures can be taken to prevent the failure of such projects and put them on the path to success. Considering the factors that have hindered the realization of BIM in construction projects, it can be said that building information modeling in construction projects needs the support of senior managers to implement it, which in itself depends on the reasons mentioned. Because by removing the obstacles in front of it, in order to optimally manage resources and time, etc., managers may be willing to use it.